Cyanidin-3-O-glucoside protects against cadmium-induced dysfunction of sex hormone secretion via the regulation of hypothalamus-pituitary-gonadal axis in male pubertal mice. (July 2019) - Li, Xusheng; Guo, Jingting; Jiang, Xingwei; Sun, Jianxia; Tian, Lingmin; Jiao, Rui; Tang, Yunge; Bai, Weibin
Abstract: Cadmium (Cd) has been generally recognized as an endocrine-disrupting chemical for its toxic effects on the hypothalamus-pituitary-gonadal (HPG) axis accompanied by dysfunction in sex hormone secretion. Particularly, exposure to Cd during puberty versus post-puberty exhibits differing age-dependent effects that require further examination. This study sought to determine if cyanidin-3-O-glucoside (C3G), a typical anthocyanin with neuroprotective bioactivity, could protect against Cd-induced sex hormone-disorder in Pubertal male mice. C3G treatment reversed the disruption of hormone levels and increased Gnrh1 gene expression in the hypothalamus. In addition, the levels of gonadotropins, including luteinizing hormone (LH) and follicle stimulating hormone (FSH), were reversed by C3G. Interestingly, C3G improved the expression of LH and FSH receptor in the testis in mice exposed to Cd. Furthermore, C3G activated the signaling pathway related to the synthesis of testosterone processing. In conclusion, C3G protected against Cd-induced dysfunction of sex hormone secretion through the regulation of the HPG axis in male mice during puberty. The results of this study suggest that consumption of anthocyanins can be protective against metal-induced male reproductive dysfunction. Graphical abstract: Image 1 Highlights: Cd-exposure increases testosterone in puberty, which differ from that in maturity. Consumption of C3G reorganizes the dysfunction of sex hormone secretion caused by Cd. C3G regulates the hypothalamus function for a normal synthesis and secretion of GnRH. C3G ameliorates the testosterone synthesis related pathway for a normal level.